Analisa Cross Cultural Pada Perusahaan Microsoft - Alif Ananda P; Calvin Owen; Fikra Terisha A; Gilbert Chryshologus; Antony Sentoso (CiDEA Journal, 2023)
In the era of globalization, effective cross-cultural management is crucial for organizations operating in diverse environments. This study examines the cross-cultural dynamics within Microsoft, a multinational technology company with a global workforce. Utilizing the frameworks of Hofstede and Trompenaars, along with insights into corporate culture types and organizational structures, the analysis delves into the cultural dimensions influencing Microsoft's operations. The study aims to provide a comprehensive understanding of how Microsoft navigates cultural diversity in its global business environment, shedding light on the formation of core values and organizational behaviors. Through an in-depth examination, the analysis explores the implications of cross-cultural aspects on human resource management strategies, such as recruitment, performance management, and career development. Insights gained from this study can contribute to Microsoft's sustained global success by informing strategies related to cultural training, onboarding programs, and global rotations. Ultimately, understanding and managing cross-cultural nuances within Microsoft are imperative for fostering integration, collaboration, and optimal productivity among employees from diverse backgrounds and for guiding successful expansions and acquisitions in culturally distinct regions.